2004
DOI: 10.1038/sj.onc.1207895
|View full text |Cite
|
Sign up to set email alerts
|

Human SNM1B is required for normal cellular response to both DNA interstrand crosslink-inducing agents and ionizing radiation

Abstract: DNA interstrand crosslinks (ICLs) are critical lesions for the mammalian cell since they affect both DNA strands and block transcription and replication. The repair of ICLs in the mammalian cell involves components of different repair pathways such as nucleotide-excision repair and the double-strand break/homologous recombination repair pathways. However, the mechanistic details of mammalian ICL repair have not been fully delineated. We describe here the complete coding sequence and the genomic organization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 47 publications
(50 reference statements)
7
91
1
Order By: Relevance
“…Our own prior studies of hSNM1B have suggested a more general role for the protein in the cellular response to both DNA double-strand breaks or interstrand crosslinks [1]. In the current study, we extend these findings.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our own prior studies of hSNM1B have suggested a more general role for the protein in the cellular response to both DNA double-strand breaks or interstrand crosslinks [1]. In the current study, we extend these findings.…”
Section: Introductionsupporting
confidence: 79%
“…We have recently described hSNM1B as a new gene involved in this cellular response to DNA damage [1]. The hSNM1B protein belongs to the SNM1-family.…”
Section: Introductionmentioning
confidence: 99%
“…RSBN1 is expressed exclusively in germ cells (45). DCLRE1B is expressed ubiquitously, but its function in the cellular response to DNA intrastrand cross-links does not suggest a role in immune responses (46). On the other hand, C1orf178 is a member of the Bcl-2 family with some proapoptotic function and is expressed in both spleen and thymus (42).…”
Section: Discussionmentioning
confidence: 99%
“…Knock-out of Snm1B in chicken cells and small interfering RNA against Snm1B in human cells both result in mild sensitivity to interstrand cross-linking agents (28,29). Knockdown of Snm1B by small interfering RNA induces an increase in aberrant metaphase morphology in human cells (29).…”
mentioning
confidence: 99%
“…Knock-out of Snm1B in chicken cells and small interfering RNA against Snm1B in human cells both result in mild sensitivity to interstrand cross-linking agents (28,29). Knockdown of Snm1B by small interfering RNA induces an increase in aberrant metaphase morphology in human cells (29).The importance of Artemis on telomere stability and telomere length regulation led us to examine whether the other two DNA-binding members of the ␤-CASP family, human (h) 2 Snm1A and hSnm1B associate with telomeres. …”
mentioning
confidence: 99%